Portrait of Development Risk as a Young Defence - Arbour, Marie-Ève (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2014)
Since its (recent) insertion into the vocabulary of jurists, development risk has piqued the curiosity of experts in defective products liability. An investigation into development risk’s scope and reach, however, requires a comparative analysis that brings out the issues it raises and the ambiguities it has occasioned. In this light, this article draws support from abundant doctrine, and, perhaps paradoxically, scant jurisprudence on the subject, in an effort to sketch, in broad strokes, a contemporary portrait of development risk.